"As long as it is not irradiated" – Influencing factors of US consumers' acceptance of food irradiation. (January 2019) - Bearth, Angela; Siegrist, Michael
Highlights: The label "Treated with irradiation" lowered quality perception of foods. Despite denoting the same technology, "Ionization" did not lower quality perception. Acceptance of food irradiation is indirectly linked to affect evoked by nuclear power. Abstract: Innovative microbial decontamination strategies, such as food irradiation or treatment of foods with protective cultures, offer solutions for today's food industry to produce safe food with appropriate shelf-life and quality. However, consumers frequently exhibit strong aversions towards highly processed foods and unfamiliar and artificially-sounding food technologies. This paper aimed at examining consumers' quality perceptions of foods treated with different decontamination strategies and linking these findings to the theoretical assumptions of the affect heuristic in two online studies with US consumers (study 1: N = 184, study 2: N = 65). The main finding from study 1 was that the label "treated with food irradiation" had a detrimental effect on consumers' quality perception of different foods, while "treated with food ionization" did to a lesser degree, despite being another term for the identical decontamination strategy. The suggestion that this detrimental effect origins in negative affect and associations raised by the term "food irradiation, " was substantiated in study 2. Consumers, who have negative feelings towards nuclear power, perceive irradiated foods as lower in quality, perceived less benefits and more risks associated with food irradiation and exhibit lower overall acceptance of this technology. The findings of the two studies are discussed in light of recommendations for the food industry and regulation. This study stresses the importance of consulting with social science ahead of the implementation of a new food technology.